Maternal stress associated with juvenile idiopathic arthritis. (4th June 2014) - Cox, Angela; Ostring, Genevieve; Piper, Susan; Munro, Jane; Singh‐Grewal, Davinder
Abstract Objective To assess parental stress levels of mothers of children with juvenile idiopathic arthritis (JIA) aged between 2–12 years and compare with those reported for other chronic childhood illnesses. Methodology Mothers of children aged between 2–12 years with JIA were recruited from hospital‐based outpatient clinics. Maternal stress was measured by using the Parenting Stress Index Long Form (PSI). The physician assessing the child completed an active joint count, a physician's global assessment and recorded the C‐reactive protein and/or erythrocyte sedimentation rate if one was clinically indicated. Results The mothers recruited had children with a mean age of 6 years. The mean total stress score of mothers of children with JIA measured by the PSI was 235.4 (95% CI 218.5–252.3) was greater than the mean total stress scores for mothers of normal children at 222.8 (95% CI 221.4–224.2). It was also greater than children with other chronic disorders such as insulin‐dependent diabetes mellitus (IDDM), 218.1 (95% CI 204.7–231.6) and profound deafness, 221.7 (95% CI 206.4–237.0). One third of mothers had total PSI scores that were in the clinical range (Total PSI > 260), indicating a need for intervention. Conclusion JIA should be regarded as a significant illness in which maternal stress is at least equivalent to that associated with the care of children with other chronic diseases of childhood.